1982
DOI: 10.1007/bf02940140
|View full text |Cite
|
Sign up to set email alerts
|

The effect of apple fibre on diabetic control and plasma lipids

Abstract: SummaryTHE purpose of the study was to investigate the effect of apple fibre on diabetic control and on plasma lipid levels in non insulin dependent maturity !inset diabetes _mellitus. Twelve patients (8 females and 4 males) ingested 15g of apple fibre per day over a period of 7 weeks. There was a significant improvement in diabetic control, as reflected by a fall in mean fasting plasma glucose (P<0.05) and in percentage glycosylated. haemoglobin (P<0.005). There was a 5% decrease in plasma cholesterol and 4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, the HPEC diet produced a correction in lipid abnormalities observed in obese rats. Many studies have showed a clear correlation between a high-fiber diet and reduced plasma lipid levels [53,54]. However, previous studies have reported that cellulose was without effect on serum cholesterol or triglycerides levels [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the HPEC diet produced a correction in lipid abnormalities observed in obese rats. Many studies have showed a clear correlation between a high-fiber diet and reduced plasma lipid levels [53,54]. However, previous studies have reported that cellulose was without effect on serum cholesterol or triglycerides levels [55].…”
Section: Discussionmentioning
confidence: 99%
“…A slight reduction (5.6%) in plasma TC levels was found. The other available human studies with fresh apples reported an insignificant variation of plasma TC …”
Section: Discussionmentioning
confidence: 90%
“…A significant decrease (−9%) in HDL‐C from the baseline was observed in a 6‐week crossover study . The other available human studies with both fresh apples and apple products reported an insignificant variation of plasma HDL‐C . No previous data are available regarding which polyphenolic compound in apples could play a major role in the effects of apple on HDL‐C metabolism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gormley et al . (1977) showed that eating two apples daily lowered serum cholesterol, while ingesting apple fiber (15 g/day) was beneficial in treating of noninsulin dependent maturity onset diabetes mellitus, as reported by Mayne et al . (1982).…”
Section: Introductionmentioning
confidence: 77%